Vascular plants diversity in short rotation coppices: a reliable source of ecosystem services or farmland dead loss? - Fehér A (iForest - Biogeosciences and Forestry, 2020)
Short rotation coppices (SRCs) are a relatively new type of crop stand that is usually established on agricultural land in intensively used landscapes. However, SRCs also offer services other than the production of renewable energy. We evaluated the more complex significance of SRCs by including the other important potential ecosystem services of these stands. The objective of this paper was to evaluate the ecosystem services and disservices of SRCs by inductive (bottom-up) methods moving from the species-level to the ecosystem services on the basis of the spontaneous vascular plants diversity in SRCs. We also compared the plant-diversity-based potential ecosystem services and disservices of field SRCs, crops and forests in the same landscape in southwestern Slovakia. It was found that SRCs had an intermediate vascular plants species composition between those of forest ecosystems and agroecosystems. Among the ten evaluated ecosystem services and disservices, considering the sum of the positive and negative evaluations, SRCs had an intermediate position between the forests and arable-land vegetation. When comparing the ecosystem services of the SRCs with those of the forest ecosystems and agroecosystems, the SRCs achieved the best rating for species richness, remediation and collectables. SRCs had the worst rating for providing pasture and had the highest proportion of toxic and allergenic plants. Interestingly, SRCs achieved positive values in ecosystem services and mainly recorded the worst values in the ecosystem disservices. The direct utilization of these services and the economic balance of ecosystem services and disservices require further study.